Freewill associations of municipalities as a presumption for self-dependence of rural areas. Experience from Czech Republic: Present situation and perspective - Ježek, Jiři (Journal for Geography, 2006)
The paper deals with an analysis of a current state and perspectives of voluntary associations of municipalities and towns, so-called microregions in the Czech Republic. It analyses problem fields and identifies factors which influence effective function of the microregions. In the conclusion of the article we mention some recommendations, which should lead to more effective activities of microregional cooperation, as a significant assumption of mainly rural areas development. The paper is the output of the solution of the Ministry for Local Development´s project ‘Regional management like a way to sustainable development of rural areas‘.